Potential of salak (Salacca sumatrana) peel extract as a reducing agent for silver nanoparticle synthesis - Azis H. Riyadi; Purwiyatno Hariyadi; Nugraha E. Suyatma; Sri Yuliani (Institution for Industrial Research and Standardization of Industry - Padang, 2023)
Salak peel extract has a potential to be used as a natural reducing agent in the synthesis of silver nanoparticles (AgNPs). The salak peel (SP) used contained 0.082 and 0.031 % on a dry basis of phenolic and flavonoids compounds, respectively. AgNPs were synthesized by reacting AgNO3 1 mM with the SP extract; with and without heating at 60oC for 10 minutes; followed by incubation for 1 to 6 days at room temperature. The addition of NaOH as a catalyst agent was also evaluated. Surface Plasmon Resonance (SPR) spectra patterns were observed using UV-Vis spectrophotometer. The resulting silver nano colloid exhibited an SPR spectrum in the wavelength range 400 – 450 nm. The absorbance value of the SPR spectrum increased temperature, alkali, and increased amount of SPE (Salak Peel Extract). FTIR spectra confirmed that the phenolics and flavonoids in the salak peel become the major component of reducing compounds in forming AgNPs. This study proves the chemical components of SP that are potentially used as bio-reductor of AgNP synthesis.